Domestic Economy in the school. Women’s education: programs and textbooks (Argentina, 1870- 1920) - Rodriguez, Laura Graciela (Historia y Memoria de la Educación, 2021)
In Argentina, starting in the year 1870 the first national Normal Schools (Teacher Training Schools) were created at the initiative of Domingo F. Sarmiento. As in other countries, the expansion of Normal Schools responded to the need to train teachers in order to give instruction to the majority of the population, to provide moral guidance to popular sectors, to transmit basic principles of hygiene, and to help make them part of the same national community. In these nascent modern states, functionaries also had to take care of providing a differentiated education to girls, so that they would learn to be good wives, mothers and housewives, through the transmission of content prepared especially for them. Imitating countries such as the United States, France or Belgium, the subject Domestic Economy was included in Normal Schools and primary schools. In this article we will discuss: a) how the subject was incorporated into the curriculum developed for the primary schools of the province of Buenos Aires as well as the capital city, what the course loads consisted of, and how they evolved; b) what content and purposes the programs pursued; c) what topics were dealt with in the texts selected by the official authorities; d) and how the subject was taught in the classroom.